Formaldehyde Measurements: A Bibliometric Analysis and Systematic Literature Review - Satya Cantika Agustinur; Riski Ramadani (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2024)
Formaldehyde is a dangerous air pollutant with severe health impacts. It can cause respiratory issues such as coughing, shortness of breath, and chest pain. In extreme cases, it can even lead to fluid buildup in the lungs, a condition that can be life-threatening. Formaldehyde can be measured using various chemical analysis methods, ranging from classical methods to modern instrument-based techniques, such as specific chemical reagents that react with formaldehyde, spectroscopy, chromatography, and electronic-based sensor techniques. This research aims to provide a comprehensive overview of the evolution of research related to formaldehyde measurements, especially relative humidity. This type of research is a systematic literature review (SLR) using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) method. The database used was Scopus, covering the years 2014 to 2023, and obtained 3,489 documents. The literature review results show a significant influence between relative humidity (RH) and formaldehyde emissions from various building materials, such as paint, wood panels, and furniture materials. The consistency of these findings suggests that relative humidity influences the amount of formaldehyde released into indoor air.